Biomedical sciences : essential laboratory medicine - Docherty, Suzanne M.; Iles, Raymond K. (Wiley-Blackwell, 2012)
'Biomedical Sciences' is an indispensable, all encompassing core textbook for first and second year biomedical science students that will support them throughout their undergraduate career